Structure and variability of the abyssal water masses in the Ionian Sea in the period 2003‐2010. Issue 2 (26th February 2013) - Bensi, Manuel; Rubino, Angelo; Cardin, Vanessa; Hainbucher, Dagmar; Mancero‐Mosquera, Isaac
Abstract : [1] This study presents aspects of the spatial and temporal variability of abyssal water masses in the Ionian Sea, as derived from recent temperature, salinity, dissolved oxygen and velocity observations and from comparisons between these and former observations. Previous studies showed how in the Southern Adriatic Sea the Adriatic Deep Water (AdDW) became fresher (ΔS ≈ −0.08) and colder (ΔT ≈ −0.1°C) after experiencing warming and salinification between 2003 and 2007. Our data, collected from October 2009 to July 2010 from two bottom moorings, one within the Strait of Otranto and the other in the northern Ionian, confirm this tendency: a bottom vein of southward‐flowing AdDW, whose temperature and salinity continuously decreased during the observation time, was detected there. Typically, the vein travel time between the two stations ranged between 45 and 50 days. This gave us a temporal estimate for AdDW anomaly propagation towards the Ionian abyss from their Adriatic generation region. The density excess of the observed vein was always enough to enable its existence as a bottom‐arrested current. This evidence confirms that, at that time (2009 and 2010), the Adriatic Sea was greatly contributing to the formation of Eastern Mediterranean Deep Water (EMDW), the bottom water of the Eastern Mediterranean. Hence, based on these results and on the evidence that, from 2003 to 2009, abyssal Ionian waters became saltier and warmer under the time‐lagged influence of AdDW, possible future changes in the EMDW characteristics, as a response to Adriatic variability, are discussed. Key Points: Recent Changes in the abyssal Ionian Sea Adriatic outflow spatial and temporal variability The response of the abyssal Ionian Sea to the Adriatic Sea variability